Supersolids of Hard Core - Bosons on a Triangular Lattice - Thang, Nguyen Toan; Nga, Pham Thi Thanh (Communications in Physics, 2011)
We study the boson model on a triangular lattice interacting only via on-site hardcore repulsion by mapping to a system of spins (S = 1/2). We investigate the supersolid phase of the systems which is a state matter displaying both diagonal long- range (solid) order as well as off-diagonal long-range (superfluidity) by utilizing a semionic representation for the spin-XXZ model. We show that the supersolid order is stable in the mean-field theory for a broad region of parameters. The inclusion of spin wave corrections modifies this picture, but the supersolid phase is still quite robust on the triangular lattices.